2013
DOI: 10.2135/cropsci2012.11.0632
|View full text |Cite
|
Sign up to set email alerts
|

Population Structure and Single Nucleotide Polymorphism Diversity of Historical Minnesota Maize Inbreds

Abstract: The University of Minnesota has developed more than 600 maize (Zea mays L.) inbreds since 1915. Our objectives were to (i) characterize the population structure and relatedness in the historical Minnesota maize inbred collection in comparison with inbreds of known heterotic groups, (ii) identify any unique germplasm groups among the historical Minnesota inbreds, and (iii) characterize the genetic diversity of the historical Minnesota germplasm. We used the Illumina MaizeSNP50 Beadchip to analyze 284 inbreds wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 27 publications
0
26
1
Order By: Relevance
“…The average Fst value was 0.069, larger than in breeding programs of the Corn Belt (Romay et al, 2013), between (Liu et al, 2015) and between elite Chinese lines and public US lines (Jiao et al, 2012). However, obtained Fst value in this study was smaller compared to Fst = 0.165 in a diverse panel of 284 maize inbreds (Schaefer, Bernardo, 2013).…”
Section: Resultscontrasting
confidence: 68%
See 1 more Smart Citation
“…The average Fst value was 0.069, larger than in breeding programs of the Corn Belt (Romay et al, 2013), between (Liu et al, 2015) and between elite Chinese lines and public US lines (Jiao et al, 2012). However, obtained Fst value in this study was smaller compared to Fst = 0.165 in a diverse panel of 284 maize inbreds (Schaefer, Bernardo, 2013).…”
Section: Resultscontrasting
confidence: 68%
“…Wu et al (2015) revealed clustering patterns of 1857 maize accessions from around the world represented by Mo17, B73, 207, Oh43 and A634 (containing 87.5% of B14 germplasm), several Chinese lines, Reid Yellow Dent, tropical and subtropical germplasm. The B73, Mo17, Oh43, PH207 and A321 maize subpopulations were identified with SSR and SNP markers by Schaefer and Bernardo (2013). Pedigree information and shared allele frequencies of the inbred lines developed at the Institute of Field and Vegetable Crops, Serbia and the referent historical lines, such as B73, Mo17, B14 and PH207, showed a considerable contribution of these ancestor-inbreds to in the lineage of the modern inbred lines and indicated the importance in maize breeding in the southeast Europe.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results have been reported in studies conducted by Yan et al (2010), who reported seven clusters obtained by using 1362 SNP markers. Schaefer and Bernardo (2013) reported the effectiveness of SNP markers as they managed to group 284 maize inbreds into five clusters. Yang et al (2011) reported that the same clusters were observed by using both SSR and SNP markers.…”
Section: Genetic Distancementioning
confidence: 99%
“…For U.S. maize breeding, three main heterotic groups, i.e., Iowa Stiff Synthetic (SS), Non-Stiff Stalk (NSS) and Iodent (IDT), were formed in the late 1950s and constitute genetically distinct breeding pools today [3], with representative lines of B73, Mo17 and 207, respectively. Integrated with the pedigree information and high-throughput molecular makers, the current maize germplasm is further divided into Oh43, Lancaster, Oh07-Midland, Iodent, SS, commercial hybrid-derived groups, Argentine Maize Amargo background groups [3], A321, 207 [17], Tangsipingtou (TSPT), Ludahonggu (LDHG), Modified Reid, Lancaster, and P group [18, 19]. Common groups of B73, Mo17, 207, and HZS have been observed in different reports [4, 18, 20, 21].…”
Section: Introductionmentioning
confidence: 99%